A Case Study Of Al Rajhi Bank - Yi, Chen (2008)
Al Rajhi Bank is a major name in Saudi Arabia's banking and business world. It has grown from a strong base, focusing on serving the needs of the nation and its citizens, contributing to the Kingdom's construction and development, and always operating within the framework of Shariah principles.